THE IMPACT OF MACROECONOMIC INDICES UPON THE LIQUIDITY OF THE BALTIC CAPITAL MARKETS - Paškevičius, Arvydas; Norkaitytė, Ona (Ekonomika, 2011)
The present paper addresses the issue of the interaction of a range of macroeconomic indices upon the liquidity of Lithuanian, Latvian and Estonian capital markets, and includes a survey of the factors having an effect upon the processes. The analysis of the liquidity in the markets concerned in the period from 2001 to 2010 was performed with reference to indicators based on trading volumes in these markets. The correlation analysis performed for the purpose of the present paper showed that changes in a number of macroeconomic indicators, such as GDP, unemployment levels, trade and service balance, also the FDI flows, produced the most tangible impact upon the liquidity of the Baltic capital markets.